Intestinal Health in Broiler Chickens Treated with Nanoencapsulation of Terminalia catappa Leaf Extract as an Antibacterial Agent - N. A. Hidayati; Zuprizal; Kustantinah; R. E. Indarto; E. Suryanto; N. D. Dono (Tropical Animal Science Journal, 2022)
This study aimed to observe the characteristics of nanoencapsulation of Terminalia catappa leaf extract (NETLE) in drinking water as an antibacterial agent and its effects on growth traits, intestinal microflora population, and intestinal micromorphology in broiler chickens. In this study, as many as 192 male broiler chickens were kept in a semi-closed house and distributed into six treatments with four replications, each replication consisting of eight birds, with the experimental treatments consisting of water without any additive (T0; negative control), water added with 50 ppm antibiotics tetracycline (T1; positive control), water added with 15 mL/L T. catappa leaf extract (T2), water added with 30 mL/L T. catappa leaf extract (T3), water added with 15 mL/L NETLE (T4), water added with 30 mL/L NETLE (T5). The diet consisted of yellow corn and soybean meal with 22.09% crude protein, 3155.05 kcal/kg metabolizable energy, 1.10% calcium, and 0.67% available phosphorus. The study showed that the size of NETLE was 77.2 nm with a Polydispersity Index of 0.417 and a zeta potential value of +44.8 mV. It proved that NETLE had antibacterial activity against Escherichia coli, Salmonella typhimurium, and Lactobacillus acidophilus. The administration of NETLE in drinking water did not affect growth performance, villus width, and crypt depth, yet reduced Salmonella sp. population (p<0.01) and increased lactic acid bacteria population (p<0.01), villus height (p<0.01), and the ratio of villus height to crypt depth (p<0.05). The findings showed the beneficial function of NETLE additions in drinking water to improve histomorphology and reduce pathogens in the intestinal of broiler chickens.